Exploring institutional structures for Tidal River Management in the Ganges-Brahmaputra Delta in Bangladesh - Gain, Animesh K.; Ashik-Ur-Rahman, Md; Benson, David (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
Tidal River Management (TRM) is a local adaptation strategy for coastal floodplains in the Ganges-Brahmaputra Delta in Bangladesh. TRM involves the periodic opening and closing of embankments to accelerate land accretion (or reclamation) in a floodplain. Although the approach is considered a promising adaptation strategy, there have been both positive and negative outcomes from recent TRM implementation. The aim of this study is consequently to explore the institutional (community, rules-in-use, and also biophysical) factors influencing successes and failures of TRM implementation for managing common-pool resources, as a basis for making recommendations on future institutional design. The Institutional Analysis and Development (IAD) framework, first developed by Ostrom (2010) and revised by Bisaro and Hinkel (2016), is therefore used to conduct comparative analysis of TRM institutional effectiveness in three Delta floodplains or beels: one led by a local community and the other two by national authorities. Our research employs a mixed method approach involving focus group discussions, stakeholder interviews, site visits, along with secondary literature analysis. The results of this assessment provide insights into coastal adaptation governance that could inform TRM implementation in Bangladesh and other similar contexts worldwide.